PERAN PEMERINTAH DESA DALAM PENCEGAHAN DAN PENANGGULANGAN PENCEMARAN DAERAH ALIRAN SUNGAI CITARUM (Studi Kasus di Desa Nanjung Kabupaten Bandung) - Septiansyah, Bayu; Kushartono, Toto; Nabila, Azhkia Carissa (Jurnal Academia Praja, 2024)
The losses suffered from decades of pollution of the Citarum River are enormous. Starting from the damage to the Upper Citarum Watershed (DAS) to industrial and domestic waste pollution. In an effort to improve the water quality of the Citarum River, the central government launched a program called the Citarum Harum Program through Presidential Regulation (Perpres) No. 15 of 2018, this program is targeted to be completed for a period of 7 years since the initial issuance of the policy. The research used a qualitative method approach with the research location in Nanjung Village in Bandung Regency. The data collection techniques were interviews, observation and documentation. The results of this study show that the role of the village government in preventing and overcoming pollution of the Citarum River Basin in Nanjung Village is trying its best although it has not been able to have a significant impact on the community and still experiences several obstacles, one of which is the absence of a strong legal umbrella for the village government. A strong legal umbrella is needed so that the community can act decisively.